Aerobic exercise does not affect serum neurofilament light in patients with mild Alzheimer’s disease - Frederiksen, Kristian Steen; Jensen, Camilla Steen; Høgh, Peter; Gergelyffy, Robert; Waldemar, Gunhild; Andersen, Birgitte Bo; Gottrup, Hanne; Vestergaard, Karsten; Wermuth, Lene; Søndergaard, Helle Bach; Sellebjerg, Finn; Hasselbalch, Steen Gregers; et al. (Frontiers in Neuroscience, 2023)
Introduction Aerobic exercise has been shown to modify Alzheimer pathology in animal models, and in patients with multiple sclerosis to reduce neurofilament light (NfL), a biomarker of neurodegeneration. Objective To investigate whether a 16-week aerobic exercise program was able to reduce serum NfL in patients with mild Alzheimer’s disease (AD). Methods This is a secondary analysis of data from the multi-center Preserving Cognition, Quality of Life, Physical Health, and Functional Ability in Alzheimer’s disease: The Effect of Physical Exercise (ADEX) study. Participants were randomized to 16 weeks of moderate intensity aerobic exercise or usual care. Clinical assessment and measurement of serum NfL was done at baseline and after the intervention. Results A total of 136 participants were included in the analysis. Groups were comparable at baseline except for APOEε4 carriership which was higher in the usual care group (75.3 versus 60.2%; p = 0.04). There was no effect of the intervention on serum NfL [intervention: baseline NfL (pg/mL) 25.76, change from baseline 0.87; usual care: baseline 27.09, change from baseline −1.16, p = 0.09]. Conclusion The findings do not support an effect of the exercise intervention on a single measure of neurodegeneration in AD. Further studies are needed using other types and durations of exercise and other measures of neurodegeneration. Clinical trial registration clinicaltrials.gov, identifier NCT01681602.